COMBINATION OF BASIL, TURMERIC AND BEAN SPROUTS TO HEMATOLOGY AND BIOCHEMISTRY OF FEMALE RAT BLOOD BEFORE PREGNANCY - Andriyanto, Andriyanto; Mustika, Aulia Andi; Manalu, Wasmen; Subangkit, Mawar; Aurelia, Sharon; Widi, Leliana Nugrahaning; Putra, Hamdika Yendri; Tarigan, Elpita; Irarang, Yusa (Jurnal Kedokteran Hewan, 2023)
The purpose of the study was to examine the safety of combination of basil, turmeric and bean sprouts extract solution on the hematological parameters and blood biochemistry profile of rats. The combined ingredients used in the study were obtained from different places. A total of 15 rats were divided into 3 groups based on the treatment dose. Each group consisted of 5 rats. The rats in control group (K) did not given extract combination, while the rats in group KKT 1 % and KKT 5% received combination of basil, turmeric and bean sprouts extract at dose of 1% and 5%, respectively. Effectiveness and safety tests were carried out by evaluating the hematological and blood biochemical profiles of female rats. The data were analyzed using one-way analysis of variance (ANOVA). The results showed that the rats given combination of basil, turmeric and bean sprouts extract at a dose of 1% and, dose of 5% did not had significant different compared to control (P0.05), but tend to have positive effects in increasing several blood components that play an important role in maintaining immunity during pregnancy. It can be concluded that the combination of basil, turmeric and bean sprouts at dose of 1% and 5% do not adversely affect hematology profile and blood biochemistry of rats. This indicates that the extract combination does not cause any toxicity effects on the rats.